Dissensus in collaborative governance: Future challenges of Lampung’s capital relocation policy - Maulana Mukhlis; Teuku Fahmi; Ulfa Umayasari (Journal of Governance and Accountability Studies, 2026)
Purpose: The find out whether there is dissensus and its implications for the experience of policy failure. Analysis of these factors is an important note in the anticipatory government framework for the future of the policy. Methodology/approach: Descriptive research with a qualitative approach and analysis. Primary data was obtained by conducting interviews with several informants. Secondary data was obtained from tracing reports and research and regulations related to the topic of collaborative governance challenges that are directly related to the research. Results/findings: The results showed that dissensus occurred from the planning to the implementation stages. Furthermore, the lack of guarantees that collaborators' actions corresponded with the consensus led to dissensus. This condition allowed collaborators to pursue self-interests, viewing collaboration as a means to achieve economic objectives and mutually strategize. Conclusions: The involvement of the parties with the consensus before the policy is implemented still leaves the challenge of the dissensus which has the potential to be a factor that influences the failure of the policy. Limitations: This research is based on the experience of policy failures several years ago. Therefore, in the current situation, it is very possible that there will be a change in collaborators. Contribution: By analyzing the factors that lead to policy failure, this research offers important insights into the challenges faced in multi-stakeholder decision-making processes. The findings are expected to serve as a reference for policymakers to develop more effective strategies for government and stakeholder collaboration in the future.